2-DIMENSIONAL GEL ELECTROPHORESIS PROFILES OF HEMOLYMPH OF HORSESHOE CRABS TACHYPLEUS GIGAS AND CARCINOSCORPRIUS ROTUNDICAUDA - DASH, BISNU PRASAD; PATI, SIDDHARTH; MOHANTY, BIMAL PRASANNA; MAHANTY, ARABINDA (Journal of the Inland Fisheries Society of India, 2021)
Horseshoe crabs are members of the Limulidae family and are considered ’living fossils’ as these have undergone very little change from their fossilized ancestors in the last 450 million years (Kin and BÅ‚aÅ¼ejowski 2014). Presently, four species of horseshoe crabs are found in the world. The Atlantic horseshoe crab Limulus polyphemus and the Asian horseshoe crabsÂ Tachypleus gigas, Tachypleus tridentatus, andÂ Carcinoscorpius rotundicauda out of whichÂ Tachypleus gigas and Carcinoscorprius rotundicauda are found in the coast of Balasore, Odisha (Pati et al., 2015; Pati and Dash 2016). While the biology of the Atlantic Horseshoe Limulus polyphemus has been extensively studied and its blood (hemolymph) has found a number of medical applications, very less studies have been carried out on its Asian counterparts. In this context, a preliminary study has been carried out to generate the one and two-dimensional gel electrophoresis profiles of the hemolymph proteins of Tachypleus gigas andÂ Carcinoscorprius rotundicauda.